2015
DOI: 10.7314/apjcp.2015.16.15.6681
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Involving Skin, Soft Tissue and Skeletal Muscle: Benign, Primary Malignant or Metastatic?

Abstract: Background: Metastatic cancer with invasion of skin, soft tissue and skeletal muscle is not common. Examples presenting as soft tissue masses could sometimes lead to misdiagnosis with delayed or inappropriate management. The purpose of current study was to investigate clinical characteristics in the involvement of metastatic cancer. Materials and Methods: A total of 1,097 patients complaining of skin or soft tissue masses and/or lesions were retrospectively reviewed from January 2012 to June 2013. Tumors invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…11 In present study, the malignant lesions predominantly seen in skin and soft tissues was basal cell carcinoma followed by cutaneous squamous cell carcinoma. This was in accord with observation of Hsieh CY et al 16 Oral cavity lesions constituted 20.69% of present study and were found to be more common in males. The most common site of involvement was buccal mucosa followed by lip and tongue.…”
Section: Discussionsupporting
confidence: 82%
“…11 In present study, the malignant lesions predominantly seen in skin and soft tissues was basal cell carcinoma followed by cutaneous squamous cell carcinoma. This was in accord with observation of Hsieh CY et al 16 Oral cavity lesions constituted 20.69% of present study and were found to be more common in males. The most common site of involvement was buccal mucosa followed by lip and tongue.…”
Section: Discussionsupporting
confidence: 82%
“…Hsieh et al also performed an analysis of soft tissue masses, showing significantly lower malignancy rates. In contrast to our study, lesions of all sizes and especially tumors of the skin were included [14]. Overall, the results of our study show that, despite relatively low rates of malignancy, even smaller lesions should be considered as potentially malignant [6,11].…”
Section: Discussionmentioning
confidence: 60%
“…Despite the fact that soft tissue comprises about half of our total body mass, distant metastases to these areas are rare and account for about only 0.36% of all soft-tissue tumors [ 8 ]. Most cases found in the literature result from either single reports or small case series.…”
Section: Discussionmentioning
confidence: 99%